Senior Loken syndrome with Atypical Retinitis Pigmentosa: a rare manifestation of rare disease - S., Madhura; ., Sowrabha; ., Manjunath; M. R., Savitha (International Journal of Contemporary Pediatrics, 2018)
Senior Loken syndrome is an autosomal recessive condition characterized by combination of nephronophthisis and retinal degeneration. The earliest presenting features include polyuria and polydipsia secondary to impaired urinary concentrating ability. Nephronophthisis progresses to end stage kidney disease (ESKD) during second decade. The treatment of choice for ESKD due to nephronophthisis is renal transplantation. Retinal lesions are variable ranging from severe infantile onset retinal dystrophy to more typical retinitis pigmentosa. There is a spectrum of other features associated with this condition including skeletal, dermatological and cerebellar anomalies. Till date very few cases have been reported due to lack of awareness of this rare condition. Here, we report a case of Senior loken syndrome with atypical retinitis pigmentosa in a 14-year-old boy.